2014
DOI: 10.1186/s12884-014-0367-1
|View full text |Cite
|
Sign up to set email alerts
|

Team training in obstetric and neonatal emergencies using highly realistic simulation in Mexico: impact on process indicators

Abstract: BackgroundIneffective management of obstetric emergencies contributes significantly to maternal and neonatal morbidity and mortality in Mexico. PRONTO (Programa de Rescate Obstétrico y Neonatal: Tratamiento Óptimo y Oportuno) is a highly-realistic, low-tech simulation-based obstetric and neonatal emergency training program. A pair-matched hospital-based controlled implementation trial was undertaken in three states in Mexico, with pre/post measurement of process indicators at intervention hospitals. This repor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
67
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 71 publications
(73 citation statements)
references
References 25 publications
4
67
1
1
Order By: Relevance
“…These results complement process indicator findings, which concluded that PRONTO training positively impacts trained providers’ knowledge and self-efficacy and promotes goal achievement 33. Other studies in low-resource settings have also found that provider simulation-based training can positively impact maternal and/or neonatal health outcomes 34,35.…”
Section: Discussionsupporting
confidence: 71%
“…These results complement process indicator findings, which concluded that PRONTO training positively impacts trained providers’ knowledge and self-efficacy and promotes goal achievement 33. Other studies in low-resource settings have also found that provider simulation-based training can positively impact maternal and/or neonatal health outcomes 34,35.…”
Section: Discussionsupporting
confidence: 71%
“…It would thus be beneficial to extend the duration of an educational intervention using simulation in order to strengthen a healthcare system. Successful examples include the PRONTO programme and PREVEN network 22 32. These programmes target both formally and informally educated practitioners, and focus on patient outcomes and the development of a network of trained healthcare workers who could potentially pass on the knowledge.…”
Section: Discussionmentioning
confidence: 99%
“…This showed that neonatal mortality reduction was statistically significant after training with static manikins 21. Another simulation-based neonatal resuscitation training programme, PRONTO, included a team training component aimed at improving the clinical team's response to a neonatal emergency and was implemented in Guatemala after being tested in the UK 22. These are two well-known HICs-funded programmes that show the positive benefits of context-specific simulation use—low technology manikins for low-resource settings, but with high impact.…”
Section: Introductionmentioning
confidence: 99%
“…[16][17][18][19] The PRONTO training kit, the PRONTOPack, includes a hybrid birth simulator called a PartoPants™ (a modified pair of surgical scrubs with anatomical landmarks necessary for delivery) worn by a patient actress (one of the female providers). [16][17][18][19] The PRONTO training kit, the PRONTOPack, includes a hybrid birth simulator called a PartoPants™ (a modified pair of surgical scrubs with anatomical landmarks necessary for delivery) worn by a patient actress (one of the female providers).…”
Section: Study Site and Interventionmentioning
confidence: 99%
“…We used provider trainings based on the methodology developed by PRONTO International: a low-tech, highly realistic simulation and team training with facilitated debriefing, to improve identification and management of obstetric and neonatal emergencies and team functioning. [16][17][18][19] The PRONTO training kit, the PRONTOPack, includes a hybrid birth simulator called a PartoPants™ (a modified pair of surgical scrubs with anatomical landmarks necessary for delivery) worn by a patient actress (one of the female providers). The patient actress brings the patient to the center of the care and allows for direct discussion about patient experiences.…”
Section: Study Site and Interventionmentioning
confidence: 99%